Strategi Kepala Sekolah dalam Membentuk Karakter Religius Peserta Didik Melalui Budaya Sekolah di Sekolah Dasar - Aulia Nurul Fajariyah; Sholehuddin (Syntax Literate, 2023)
SD Muhammadiyah 12 Pamulang and SDIT Al Azkar Pamulang both have the same core goal, which is to create a generation of people with religious character. Religious character values are character values that are used as references as obedient attitudes and behaviors towards carrying out religious teachings. Religious character is needed by students in the face of such rapid changes in the times. The purpose of the study is to determine the strategies, supporting and inhibiting factors, as well as the formation process that the principal applies to shape the religious character of students through school culture. This study used descriptive qualitative research methods conducted at SD Muhammadiyah 12 Pamulang and SDIT Al Azkar Pamulang. Research data collection techniques with observation, interviews, and documentation with data sources of the two principals. The results of the study are strategies used by the principals of SD Muhammadiyah 12 Pamulang and SDIT Al Azkar Pamulang in shaping the religious character of students through school culture, namely habituation strategies, exemplary strategies, and partnership strategies. The supporting factors for the principal of SD Muhammadiyah 12 Pamulang and the principal of SDIT Al Azkar Pamulang are educators and education staff, parents and guardians, school facilities, and foundations. Inhibiting factors are parents, environmental factors and consistent. The process of forming religious character through habituation of school culture applied to students, and the stages of planning, implementing, monitoring and evaluating school culture programs.